Land Cover Changes (1963 2010) and Their Environmental Factors in the Upper Danube Floodplain - Xu, Fang; Otte, Annette; Ludewig, Kristin; Donath, Tobias W.; Harvolk-Schöning, Sarah; Justus Liebig University Giessen (My University, 2017)
o analyze the changes in the Upper Danube Floodplain, we used aerial photos to quantify the change of landscape pattern from 1963 to 2010. We focused on typical floodplain habitats, i.e., riparian forest and floodplain grassland. We used landscape metrics and transformation matrix to explore changes in land cover structure and composition. The active floodplain experienced increasing fragmentation from 1963 to 2010. Despite an increase of aggregation, riparian forest suffered a 2.3% area loss from 1995 to 2010. Arable land in the active floodplain declined by 28.5%, while its patch size significantly increased. Elevation, distance to river and soil quality were the most relevant environmental factors for the land cover change in the floodplain. Higher soil quality or longer distance to river led to an increase of conversion from grassland into arable land; grassland patches with poorer soil quality were likely to change into riparian forest; riparian forest closer to the river and with a lower height above mean water level tended to remain stable. This comprehensive understanding of historical land cover change and environmental factors is needed for the enhancement of landscape functions and sustainable development in the floodplain.
Keywords: riparian landscape; landscape pattern; landscape dynamics; disturbance; ddc:710